Investigation into material resistance factors and properties of young, engineered Eucalyptus grandis timber. (10th January 2020) - Pagel, Calvin L.; Lenner, Roman; Wessels, C. Brand
Highlights: The twist of the laminated of Eucalyptus grandis appears to be greatly restrained. A material reduction factor φ M of 0.77 can be utilised. Lamination results in a higher structural grade yield of material. Young engineered Eucalyptus grandis is a promising option for structural timber. Abstract: Only 1% of South Africa's total land area is used for forestry with 51% of that being used for Pinus and 40% for Eucalyptus species. A shortage of adequate structural sawn timber has been forecast where Pinus species is the predominant raw structural material and Eucalyptus is mainly used for pulp production. Young, engineered Eucalyptus grandis has been proposed as an alternative resource to mitigate the shortage of structural timber. The objectives of this study are to determine the material resistance properties and material resistance reduction factors of young, Eucalyptus grandis timber that has been finger-jointed in the green, unseasoned state and (a) is face laminated in the green state and (b) is left as a standard non-laminated set. Both groups were dried before destructive bending tests were performed. The defect development of both sets was recorded. The face lamination process did not reduce the variation in strength results to a significant extent but significantly lower grade-reducing defects, such as twist, checks and splits, were recorded for the laminated set. This results in a higher structural grade yield of material with a better visual appearance due to limited defects, thus producing a more valuable product. Additionally, based on reliability theory, a material reduction factor of 0.77 is proposed in this study in contrast to the current factor of 0.68 stipulated by the national code. This advantage, coupled with the higher structural grade achieved and the shorter rotation age than for Pinus species, make the young, green finger-jointed and face laminated Eucalyptus grandis product a promising option for structural timber use in South Africa.